PENGARUH KEPRIBADIAN, KECERDASAN EMOSIONAL, DAN PERILAKU KEWARGAAN ORGANISASI TERHADAP KINERJA KEPALA SEKOLAH MENENGAH ATAS DAN KEJURUAN DI KOTA TANGERANG - Edi Riadi (Jurnal Manajemen Pendidikan, 2012)
The Objective of the research is to obtain information about the effect of personality, emotional intelligence and organizational citizenship behavior on principal’s performance of senior high school. The research was conducted to all of senior high schools principals in The City of Tangerang by using a survey method with path analysis applied in testing hypothesis. The number of 124 school Principal’s as sample was selected by proportional random sampling. The research conclude: (1). there is direct effect of personality on principal’s performance. (2). there is direct effect of emotional intelligence on principal’s performance. (3). there is direct effect of organizational citizenship behavior on principal’s performance. (4). there is direct effect of personality on principal’s organizational citizenship behavior. (5). there is direct effect of emotional intelligence on principal’s organizational citizenship behaviour. Therefore to enhance schools principal’s performance can be carried out by personality, emotional intelligence, and the organizational citizenship behaviour.